Evaluation of NOGAPS Forcing Data for PIPS 3.0 - Schweiger, Axel J. (2002)
Operational requirements dictate the use of NOGAPS forcing fields for the PIPS ice forecasting system. This study provides an assessment of the NOGAPS model output as a suitable source for atmospheric forcing fields for PIPS 3.0. Included in the study is an assessment of the errors in some of the most critical model variables. --Original contains color plates: All DTIC reproductions will be in black and white.